Alone together : law and the meanings of marriage - Regan, Milton C. (OUP E-Books., 1999)
Contemporary marriage involves complex notions of both connection and freedom. On the one hand, spouses are members of a shared community, while on the other they are discrete individuals with their own distinct interests. Alone Together explores the ways in which law seeks to accommodate tensions between commitment and freedom in marriage. Author Milton Regan suggests that only close attention to context can guide us in deciding what weight to assign to each dimension of spousal identity in a given setting. This interdisciplinary work has relevance to family law, family studies, feminist legal theory, and the debate between liberal and communitarian social theorists. -- Provided by publisher